PREVENTIVE DENTAL AND ORAL HYGIENE KNOWLEDGE AMONG PATIENTS SEEKING DENTAL CARE IN BAGHDAD, IRAQ - Fawaz Fetyan Abdulmajeed; Laith Basil Abbas (Scholar Express Journals, 2023)
Evidence has shown that an increase in knowledge about risk factors for oral disease and strong knowledge of oral health demonstrates better oral care practices that aim to promote healthy habits
Keywords: healthy habits; preventive dental; Oral health